Particle size effect of silver nanoparticles decorated single walled carbon nanotube electrode for supercapacitors - Chowdari, Bobba V. R. (2014)
Well dispersed silver nanoparticles (AgNPs) of different sizes (1–13 nm) on single walled carbon nanotubes (SWCNTs) were synthesized by a facile room-temperature deposition–precipitation process. The morphology and microstructure of samples examined by the transmission electron microscopy showed a monodispersed silver particle decorated SWCNT of 2 wt % as determined by the Rietveld phase analysis of powder X-ray diffraction patterns. The chemical state of silver determined from the binding energies of high resolution Ag 3d peaks from X-ray photoelectron spectroscopy revealed a silver (Ag0) oxidation state. Electrochemical properties were studied using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance studies. Silver decorated SWCNTs demonstrated to be effective bifunctional charge collectors and active electrode materials for a supercapacitor, exhibiting a higher specific capacitance (106 F g−1) compared to pristine SWCNT (47 F g−1). An enhancement observed with AgNP decoration is highly size-dependent and is related to the improved intertube contact resistance, electroactive surface considerations, as well as the participation of Ag in a faradaic reaction induced pseudocapacitance. Decorating the SWCNT with 1 nm AgNP doubled the energy density of the device, which on charge–discharge cycling retained 84% of the initial capacitance at the end of 8000 cycles.